Education and Social Innovation - Rasmussen, Palle (Encyclopedia of Educational Innovation, 2019)
The idea of social innovation has become increasingly popular in recent years, and as often happens with popular concepts it risks become overloaded. This happens, for instance, when social innovation is seen as the “soft” and humanistic alternative to versions of innovation dominated by science and technology. There has been a fast growing literature on social innovation, some of it in academic publications but perhaps most of it published by think tanks, semigovernmental agencies, and other organizations. Many different institutional fields for social innovation are discussed in the literature (Moulaert et al. 2013). Education is one of them, but much less frequently treated than fields like housing, intercultural relations, environmental issues, and childcare.
Keywords: Ouvrages de référence; Réservé UdeM; Sciences de l'éducation